Stable atlantic deep water mass sourcing on glacial-interglacial timescales - Pöppelmeier, Frerk; Gutjahr, Marcus; Blaser, Patrick; Schulz, Hartmut; Süfke, Finn; Lippold, Jörg (Geophysical research letters, 2021)
Increased deep ocean carbon storage is often invoked as the major sink for lower atmospheric CO2 concentrations during past ice ages. In order to improve the understanding of the changes in ocean dynamics facilitating such increased oceanic carbon storage, we assess the variability of deep water provenance in the Atlantic by reconstructing authigenic Nd isotopes from North Atlantic site U1313 over the past ∼100 kyr. Under consideration of these new constraints for the northern Nd isotope end-member, we find only limited long-term variations in the meridional and intra-basin water-mass gradients suggesting a prevalence of northern-sourced water (NSW) throughout the past 100 kyr. Tentative results suggest that during the glacial period of Marine Isotope Stage 4 NSW proportions even increased by additional ∼15% in the equatorial and Northeast Atlantic, calling into question the notion that cold climates promote the expansion of southern-sourced water.